A STUDY ON BRENTANO’S CONCEPT OF INTENTIONALITY - Singh, Laishram Omorjit; Sharma, L. Bishwanath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In his famous book, Psychology from an Empirical Standpoint’, Franz Brentano recovers intentionality as an essential foundation of empirical psychology known as descriptive psychology. For him, intentionality is the property of consciousness or mind which is the modern equivalent of the Scholastic term, intentio’ whereby it refers to or intends an object. In the enquiry on Brentano’s concept of intentionality, the notion of the intentional (or mental) inexistence of an object undoubtedly occupies the central position. The expression, ‘inexistence’ which is his translation of the medieval Scholastic term, ‘inesse’ meaning ‘being-in’ or ‘indwelling’ refers to the inherence of property in a substance, e.g., the manner in which redness resides in the red rose or knowledge resides in the knower. Here, the concept, in’ does not have spatial connotation but it expresses dependence. Thus, the intentional object can be regarded as the real object as thought by the mind but not as a special object with inexistence. He, no doubt, enriches the concept of intentionality by providing a clear-cut criterion for distinguishing thought from non-thought, mind from non-mind, the philosophical from the non-phylosophical on the basis of an intelligible distinction between the intentional and non-intentional. In a nutshell, the term intentionality in a philosophical sense indicates an act’s being directed at an object. The aim of the paper is to examine Brentano’s concept of intentionality as propounded in ‘Psychology from an Empirical Standpoint’.